Chemical, biological and in silico assessment of Ocimum viride essential oil. Issue 6 (June 2020) - Bhagat, Madhulika; Sangral, Monica; Kumar, Ajay; Rather, Rafiq A.; Arya, Khushboo
Abstract: Aims: Ocimum viride Willd. (family: Lamiaceae ) is a member of the genus Ocimum, an aromatic annual and perennial herb with numerous culinary, horticultural and ethno-medicinal benefits. This study aims to explore the chemical properties of leaf essential oil (EO) from Ocimum viride and to evaluate its antimicrobial and anticancer potential. Main methods: Characterization of essential oil was done by GCMS, antimicrobial by agar well diffusion methods, in vitro cytotoxicity evaluation by MTT assay, cell death analysis was done by DNA fragmentation, cell cycle analysis, nuclear morphology analysis and molecular docking studies were also conducted. Key findings: Essential oil from aerial parts (leaf) of Ocimum viride revealed high content of oxygenated monoterpenes, notably thymol (~50%) and γ-terpinene (~18%). Further, antibacterial analysis showed that among all the evaluated bacterial species EO showed highest sensitivity against the Bacillus subtilis and was also found most effective against HT-29 colon cancer cell line with IC50 value of ~0.034 ± 0.001μL/mL. Mechanistic studies revealed that EO inhibits the growth of HT-29 colon cancer cells probably through induction of irreparable DNA damage leading to subsequent cell death in apoptotic manner. Molecular docking analysis also supports the in vitro studies conducted by indicating the interaction of thymol with Sec A protein of Bacillus subtilis cell wall as well as with Beclin protein responsible for apoptotic corpse clearance. Significance: Taken together, our results indicate that EO possesses potent antimicrobial and anticancer properties, and may find applications as effective antibacterial and in cancer therapeutics. Abstract : Essential oil; Antimicrobial agent; Biomedical materials; Antimicrobial agent; Cancer research; Pharmaceutical science; Toxicology.